Hybrid testing and modeling of a suspended zipper steel frame. - Stavridis, Andreas (Earthquake engineering & structural dynamics.)
An analytical and experimental study has been conducted to evaluate the seismic performance of a three story suspended zipper steel frame. The frame was concentrically braced and had zipper struts to transfer the unbalanced forces induced on the beams due to the buckling of the lower story braces. The experimental study was conducted with the hybrid test technique, in which only the bottom story braces of the three story frame were physically tested, while the behavior of the rest of the frame was modeled using a general structural analysis software. The paper discusse issues pertinent to the caibration of the computer model for the analytical substructure as well as for the entire frame, including the selection of an appropriate damping matrix, and the modeling of the buckling behavior of the braces and bracing connections. The analytical model of the entire frame was validated with the hybrid tests and was able to accurately capture the material and geometric nonlinearities that developed when the braces yielded and buckled. This study has demonstrated the usefulness of hybrid testing in improving analytical models and modeling assumptions and providing information that cannot be obtained from an analytical study alone. The results have shown that the suspended zipper frame can distribute the brace nonlinearity over the first two stories as intended in the design and will not have catastrophic failure under the design level earthquakes considered in this study, despite the significant inelastic deformations.